Extension actions in the COVID-19 pandemic to publicize the prevention and treatment of dental trauma - Panka Archegas, Lucí Regina; Spagnol, Fernanddo José; Devidé, Letícia; Fagundes de Oliveira, Mariane; Pereira Heck, Mary Aparecida (Guará Journal, 2023)
This study is a report on the experience of extension workers at the Federal University of Paraná (UFPR) in the prevention and treatment of dental trauma. They developed a clinical practice guide on dental trauma for dental undergraduates and professionals, digital materials on preventing tooth avulsion for schoolchildren, and an outreach event on dental trauma for students in the Community Health Agent Technical Course in Curitiba. This work was based on research in dental databases and digital books. Tooth avulsion is a prevalent occurrence among children and adolescents, requiring immediate action to preserve their teeth. Thus, a playful educational pamphlet, video, and online questionnaire were created for five public and private schools in Curitiba, Paraná, and Papanduva, Santa Catarina, reaching approximately 3,000 people, including parents, educators, administrators, and students. Project participants experienced socialization through digital contact with peers, advisors, and the community during the pandemic. and shared scientific knowledge through technological tools for the prevention and treatment of dental trauma for schoolchildren, undergraduates and health professionals.